Almond breeding programme in CEBAS-CSIC, in Murcia (Spain) - Dicenta F.; Ortega E.; Martínez-Gómez P.; Sánchez-Pérez R.; Martínez-García P.J.; Cremades T.; Egea J. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
The almond cross breeding program of CEBAS-CSIC began in 1985 with the objective of obtaining new self-compatible late flowering cultivars; since then more than 12,000 seedlings have been obtained. In 1995 the cultivars Antoñeta and Marta, which fit the established objectives, were released. Afterwards we follow the breeding programme with the objective of delay more and more the flowering time, to obtain new extra-late flowering self-compatible almonds. These new cultivars could be grown in the colder areas where the culture of almond is being expanded, without risk of frost. A lot of hectares, nowadays cultured with less profitable cultures, could be replaced by almond. In 2007 we released Penta and Tardona. Both are self-compatible (S2Sf and S5Sf, respectively) with a high level of autogamy. They are extra-late flowering, between 10 and 15 days after Ferragnès, what reduce more than 80 percent the risk of damage by frost in comparison with traditional late-flowering cultivars. Both are very floriferous and productive. While Penta matures very early, Tardona matures with Ferragnès. Both are hard shelled with 27 percent and 25 percent of kernel percentage. The kernel weight is 1 g for Penta, and smaller (0.8 g) for Tardona. Due to their extra-late flowering, they are recommended for areas with a high risk of frost. Both have been registered in the Community Plant Variety Office of the European Union.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)